2006
DOI: 10.1021/jp0574394
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Bonding of Alkanethiols on Cu(111) and Cu(100)

Abstract: The local structure of the sulfur atom of methanethiolate and ethanethiolate on the Cu(111) and Cu(100) surfaces was investigated from first principles employing the periodic supercell approach in the framework of density functional theory. On the 111 surface, we investigated the (square root 3 x square root 3)R30 degrees and (2 x 2) structures, whereas on the 100 surface, we investigated the p(2 x 2) and c(2 x 2) structures. The landscape of the potential energy surface on each metal surface presents distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
49
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 44 publications
(127 reference statements)
10
49
0
Order By: Relevance
“…In both phases the S headgroup atom lies in an off-hollow site, displaced towards the bridging site, the C-S bond being tilted relative to the surface normal by 33° in the (3x3)R30° phase and by 47° in the (2x2) phase. These conclusions are in excellent agreement with the results of Feral et al [16] who investigated only these unreconstructed models. There is one report of the observation of a Cu(111)(3x3)R30°-CH 3 S phase at low temperatures (110-140 K) [6], but at room temperature this transforms to the 4 3 1 3  L N M O Q P phase, suggesting that the (3x3)R30° phase is metastable and reconstructs with the aid of thermal activation.…”
Section: Dft Structures and Stm Imagessupporting
confidence: 92%
See 2 more Smart Citations
“…In both phases the S headgroup atom lies in an off-hollow site, displaced towards the bridging site, the C-S bond being tilted relative to the surface normal by 33° in the (3x3)R30° phase and by 47° in the (2x2) phase. These conclusions are in excellent agreement with the results of Feral et al [16] who investigated only these unreconstructed models. There is one report of the observation of a Cu(111)(3x3)R30°-CH 3 S phase at low temperatures (110-140 K) [6], but at room temperature this transforms to the 4 3 1 3  L N M O Q P phase, suggesting that the (3x3)R30° phase is metastable and reconstructs with the aid of thermal activation.…”
Section: Dft Structures and Stm Imagessupporting
confidence: 92%
“…This qualitative effect is consistent with the experimental results of the MEIS study [15], although the experimental value of 0.12±0.04 Å is significantly larger. The earlier DFT study of Ferral et al [16] led to the same value as in the present calculations.…”
Section: Computational Detailssupporting
confidence: 83%
See 1 more Smart Citation
“…Second, the model does not account for different orientations of the molecule relative to the surface normal. Density functional calculations of CH 3 S on metal (111) surfaces have found that, although the absolute binding energy is sensitive to the angle between the C-S bond and the metal surface [11], the energy barrier to translational motion of a molecule bound to the surface varies only slightly with this angle [12]. Third, although a more realistic molecular model would have included bond flexibility, only rigid molecules (i.e., molecules in which the positions of the interaction sites with respect to one another were kept constant) were considered in this paper.…”
mentioning
confidence: 99%
“…Fourth, only the binding of a single molecule on the surface is considered. Thus, interactions between adsorbate molecules, which have been shown to have a strong effect on the binding energies of alkanethiols as a function of coverage on metal surfaces [3,11], have been ignored. The results of this paper are, therefore, relevant to the low-coverage regime.…”
mentioning
confidence: 99%